SELF-ORGANIZING MAPS AS TOOLS FOR UNDERSTANDING THE GENETIC VARIABILITY OF POPULATIONS - da Silva Oliveira, Marciane; Gonçalves Santos, Iara; Damião Cruz, Cosme (Ambciências, 2022)
The maintenance of genetic diversity is fundamental to ensure the population's viability on the mid- and long-term. Because evolutionary factors (e.g., genetic drift, selection, migration, and inbreeding) can change the genetic structure of a population, it is important to understand how these factors act on populations and to infer about the maintenance of genetic diversity throughout generations. The Self-Organizing Maps (SOM) is an interesting approach to organize the genetic diversity and to highlight the effects caused by dispersive and systematic factors in populations. Briefly, the SOM algorithm maps the data, weighting similarities among inputs while keeps similar inputs close to each other in a topological map. The upside of this approach is that it organizes populations in accordance to biological principles. SOM have shown to be efficient in organizing natural or breeding populations that are subject to processes that reduce variability, such as drift, inbreeding, and selection, and to processes that increase genetic variability, such as migration.